2021
DOI: 10.21203/rs.3.rs-956609/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Change of Knee Cartilage Components in Stroke Patients with Genu Recurvatum Analyzed by Zero TE MR Imaging

Abstract: -BACKGROUND: Genu recurvatum in stroke patient hemiplegia causes readily cumulative damage and degenerative changes of knee cartilage. It is important to detect early lesions of cartilage for appropriate treatment and rehabilitation.-PURPOSE: The purpose is to provide theoretical basis for early rehabilitation of hemiplegia patients. -STUDY TYPE: Cross-sectional study. -POPULATION: 39 Stroke patients with genu recurvatum and 9 healthy volunteers. -SEQUENCE: We used zero TE double echo imaging sequence. -ASSESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[9,11] Different authors have provided different causes of Genu Recurvatum. [10,12] There are different views on causes but almost all the studies have mentioned that, irrespective of cause GR increases with weight bearing. [9,15] Though occurrence of GR is very common in patients with Stroke, there is limited evidence that provides detailed information about it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,11] Different authors have provided different causes of Genu Recurvatum. [10,12] There are different views on causes but almost all the studies have mentioned that, irrespective of cause GR increases with weight bearing. [9,15] Though occurrence of GR is very common in patients with Stroke, there is limited evidence that provides detailed information about it.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the peak amplitude of knee hyperextension (PKH) can range as high as 22 o in Stroke patients. [12] The biomechanical trend of the lower extremity is altered by long-term hyperextension of the knee, and because of the inadequacy of the load-bearing reaction in knee joint, there is leaning of body in forward direction as the stability of the standing phase is reduced. [13] Walking like this for an extended period of time, leads to knee discomfort and cartilage injury, these alterations generate an unequal distribution of internal stress in the knee join and cause cumulative damage and degenerative changes in knee cartilage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation